AİHM ve Türk Anayasa Mahkemesi’nin Kararları Işığında Hukuki Kesinlik (Belirlilik) İlkesinin İncelenmesi - (:unkn) unknown (My University, 2018)
Hukuki kesinlik ilkesi, hukukun üstünlüğünün temel görünümlerinden birisidir. Bu nedenle,“hukukun üstünlüğü” ve “hukuk devleti” bakımından bir ulusal hukuk sisteminde hukuki kesinliğintesis edilmesi kaçınılmazdır. Bu yazı, Avrupa İnsan Hakları Mahkemesi (AİHM) ile Türk AnayasaMahkemesi’nin (AYM) hukuki kesinlik yaklaşımları arasındaki farklılıkları ve benzerlikleri ortayakoymayı amaçlamaktadır. Bu sebeple, hukuki kesinliğin uygulamasının daha iyi anlaşılması için heriki Mahkemenin de konuyla ilgili olan davaları incelenmiştir. Söz konusu alandaki güncel vakalar,akademisyenlere ve uygulayıcılara ilkenin kavranması ile ilgili önemli ipuçları vermektedir.

The principle of legal certainty is one of the fundamental appearances of the rule of law. Therefore, the establishment of legal certainty in a national legal system is inevitable in terms of “the rule of law” and “state of law”. This paper aims to reveal differences and similarities between European Court of Human Rights and Turkish Constitutional Court regarding their approaches to the legal certainty. For this reason, the cases of both Courts have been reviewed for better understanding the implementation of the legal certainty. Recent cases in that field have given significant clues to the scholars and practitioners for comprehension of the principle.
The Examination of the Principle of Legal Certainty (Determinacy) in the Light of the Decisions of ECtHR and Turkish Constitutional Court
Keywords: Uluslararası İlişkiler; Hukuk